MENGATASI PERILAKU MALADJUSMENT MELALUI LAYANAN BIMBINGAN DAN KONSELING PRIBADI SOSIAL (STUDI DESKRIPTIF SMA DARUS SHOLAH JEMBER) - Ernawati, Sitti (FKIP Universitas Islam Jember, 2022)
This research is based on the phenomenon that exists in SMA Darus Sholah Jember which shows a high level of maladjustment. The purpose of this study was to determine the forms of student maladjustment behavior. This research is descriptive qualitative which produces descriptive data as it happens in the field. By using the technique of observation, interviews, and documentation. Subjects in the study were students who experienced maladjustment. The data analysis technique used is interactive and takes place continuously. The implementation of personal social guidance and counseling includes basic services, individual planning, responsive services, system support. Student responses are positive, most students feel a slow but sure change towards well adjustment, although there are students who have not felt a significant impact. Keywords: Behavioral Maladjustment, Social Personal Guidance and Counseling